Occupational Health and Safety Management System Emergency Response to Noise at LRT South Sumatra - Rian Saputra*; Amin Rejo; Joni Arliansyah (Riwayat: Educational Journal of History and Humanities, 2023)
At work there are several factors that need to be considered in occupational health and safety. On physical factors, biology, chemistry, psychology to ergonomics. One of the factors of occupational health and safety is the physical factor of noise. Noise is a sound or sound that is generated that is not wanted, namely the squeaky noise. Based on the results of interior noise insulation research at LRT train speeds of 500-2000 Hz, 89.4 - 96.3 dBA was obtained while the allowable noise NAB for humans was 85 dBA and the maximum noise NAB on the train was 80 dBA. The method used in this study is a field survey for noise sampling using the SM-20-A sound level meter. After sampling, researchers analyzed the univariate method for each independent and dependent variable conducted at 13 South Sumatra LRT stations. LRT passes through each bend with noise levels reaching 100 dB (˃85 dB), not meeting NIOSH standards at each bend. In CA2 criterion is the most dominant case with the highest level in each criterion, especially in the case of noise, therefore employees or officers should use PPE if they are in the bend area or when the train passes.